МОРФОЛОГІЧНІ ОСОБЛИВОСТІ ПЕРЕБУДОВИ СТРУКТУРИ ОПОРНО-РУХОВОГО АПАРАТУ ЗА УМОВ ПАТОЛОГІЇ (World Science, 2020)
The aim of our work was to study the scientific information and to systematize the data of domestic and foreign literature concerning the study of morphological features of restructuring of the musculoskeletal system in pathological settings.